2018
DOI: 10.11002/kjfp.2018.25.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and isoflavone content of Chaga Cheonggukjang with Lactobacillus acidophilus KCTC 3925 starter

Abstract: This study was conducted to investigate the quality characteristics and changes in isoflavone content of Cheonggukjang with added Chaga mushroom by secondary fermentation at 40℃ for 48 h with or without a starter, Lactobacillus acidophilus KCTC 3925. Cheonggukjang samples were divided into three groups: Control (unsterilized Cheonggukjang fermented without a starter), NS (unsterilized Cheonggukjang inoculated with L. acidophilus KCTC 3925), and YS (heat-sterilized Cheonggukjang inoculated with L. acidophilus K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…FCC was obtained after secondary fermentation of Chaga-Cheonggukjang at 40°C for 48 h with L. acidophilus KCTC 3925. As previously reported [24], FCC contains 28% more total isoflavone aglycones than the original Chaga-Cheonggukjang. FCC3 and FCC5, containing 3% and 5% (weight/weight) respectively, of FCC in HFD, were prepared as pellets similar to normal chow diet by Raon Bio Co. (Korea).…”
Section: Fermentation Of Chaga-cheonggukjangsupporting
confidence: 72%
See 1 more Smart Citation
“…FCC was obtained after secondary fermentation of Chaga-Cheonggukjang at 40°C for 48 h with L. acidophilus KCTC 3925. As previously reported [24], FCC contains 28% more total isoflavone aglycones than the original Chaga-Cheonggukjang. FCC3 and FCC5, containing 3% and 5% (weight/weight) respectively, of FCC in HFD, were prepared as pellets similar to normal chow diet by Raon Bio Co. (Korea).…”
Section: Fermentation Of Chaga-cheonggukjangsupporting
confidence: 72%
“…Isoflavone aglycone-rich diet can reduce liver and serum total cholesterol levels, and liver triglyceride levels in cholesterol-fed rats [42]. Our previous study demonstrated that FCC possesses 28% more isoflavone aglycones than unfermented chaga-cheonggukjang [24]. In addition, chaga extract contains water-soluble melanin complex, which plays a role in improving insulin sensitivity, and reducing adiposity in HFD mice [43].…”
Section: Discussionmentioning
confidence: 97%